Manajemen Kepala Tata Usaha di MAN 2 Kota Jambi - Bawaihi; Armida; Leni Ardianti (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2022)
This study discusses the Management of the Head of Administration of Madrasah Aliyah Negeri 2 Jambi City. The research approach that the authors use is descriptive qualitative, while data collection is carried out by Observation, Interview, Documentation. The purpose of this study is to find out how the Head of Administration in (Planning, Organizing, Implementing, Supervising) can help the Administration in improving its performance. The subjects in this study were the Head of Administration and Administrative Staff of Madrasah Aliyah Negeri 2 Jambi City. The object of this study is the Management of the Head of Administration of Madrasah Aliyah Negeri 2 Jambi City on the performance of the Madrasah Aliyah Negeri 2 Jambi City Administration. The results of this study found that the role of the head of administration has a significant impact on achieving the implementation of education in a school / madrasah. Because the existence of the head of administration plays a very important role. Administrative services will not run effectively without the role of the head of administration as a leader. In the implementation of administrative services, the head of administration is assisted by educational personnel. The condition of the administration in Madrasah Aliyah Negeri 2 Jambi City has been well organized as evidenced by the existence of a structural administrative organizational chart and the distribution of tasks in accordance with the field of subtlety. Because the administrative services of Madrasah Aliyah Negeri 2 Jambi City have been well organized, the quality of education in the school has become better, it is proven that Madrasah Aliyah Negeri 2 Jambi City has received